Microstructural changes in the brain after long‐term post‐concussion symptoms: A randomized trial. Issue 3 (15th December 2020) - Trillingsgaard Næss‐Schmidt, Erhard; Udby Blicher, Jakob; Møller Thastum, Mille; Ulrikka Rask, Charlotte; Wulff Svendsen, Susanne; Schröder, Andreas; Høgh Tuborgh, Astrid; Østergaard, Leif; Sangill, Ryan; Lund, Torben; Nørhøj Jespersen, Sune; Roer Pedersen, Asger; et al.
Abstract: A recent randomized controlled trial in young patients with long‐term post‐concussion symptoms showed that a novel behavioral intervention "Get going After concussIoN" is superior to enhanced usual care in terms of symptom reduction. It is unknown whether these interventional effects are associated with microstructural brain changes. The aim of this study was to examine whether diffusion‐weighted MRI indices, which are sensitive to the interactions between cellular structures and water molecules' Brownian motion, respond differently to the interventions of the above‐mentioned trial and whether such differences correlate with the improvement of post‐concussion symptoms. Twenty‐three patients from the intervention group (mean age 22.8, 18 females) and 19 patients from the control group (enhanced usual care) (mean age 23.9, 14 females) were enrolled. The primary outcome measure was the mean kurtosis tensor, which is sensitive to the microscopic complexity of brain tissue. The mean kurtosis tensor was significantly increased in the intervention group ( p  = 0.003) in the corpus callosum but not in the thalamus ( p  = 0.78) and the hippocampus ( p  = 0.34). An increase in mean kurtosis tensor in the corpus callosum tended to be associated with a reduction in symptoms, but this association did not reach significance ( p  = 0.059). Changes in diffusion tensor imaging metrics did not differ between intervention groups and were not associated with symptoms. The current study found different diffusion‐weighted MRI responses from the microscopic cellular structures of the corpus callosum between patients receiving a novel behavioral intervention and patients receiving enhanced usual care. Correlations with improvement of post‐concussion symptoms were not evident. Abstract : Microstructural changes in the middle brain.